La desintegración familiar y su relación con el aprendizaje de los niños y niñas del primer grado de educación general básica de la escuela fiscomisional Cacha de la provincia de Zamora Chinchipe del cantón El Pangui, periodo 2013 – 2014. Lineamientos alternativos - Medina Cajilima, Ligia Zoraya (2015)
This thesis refers to “FAMILY DECAY AND ITS RELATIONSHIP WITH LEARNING CHILDREN FIRST GRADE GENERAL EDUCATION BASIC SCHOOL FISCOMISIONAL “CACHA “PROVINCE DE ZAMORA THE CANTON CHINCHIPE Panguí, PERIOD 2013 – 2014. GUIDELINES ALTERNATIVE”. The general objective was : To determine the relationship between Family Disintegration and Learning of children , First Grade Students General Education School missionary treasury " Catcha " in the province of Zamora Chinchipe the Pangui Canton , period 2013 - 2014 " . The methods used for the preparation of this research work were : Scientist, Analytical - Synthetic, Inductive- Deductive , Statistical Model ; the techniques used were: Survey applied to the Parent in order to identify the factors that cause Family Disintegration and Observation Form that children of the first grade of elementary school Missionary School Fiscoapplied " grip "to estimate learning children . In the implementation of the survey parents concluded that: this disintegrated family: 35 % were due to machismo, 23% to emigration, 18% for addictions, 15% gave lack communication, 9% by the economic situation. According to the results of the Observation Form will reach the conclusion that 75 % reached an average of Highly Satisfactory, 14% Satisfactory and Unsatisfactory 11%.